Does cross-listing increase managers' propensity to listen to the market in M&A deals? - Abdallah, Abed AL-Nasser; Abdallah, Wissam (Journal of Corporate Finance, 2017)
We investigate the validity of two conjectures regarding the impact of cross-listing on managers' propensity to listen to the market in mergers and acquisitions (M&A) deals. The first maintains that cross-listing in the US improves price informativeness and investor protection leading managers of cross-listed firms to listen to the market when considering M&A deal. The second postulates that the lack of law enforcement by the US Securities and Exchange Commission (SEC) against foreign firms impairs cross-listing as an effective mechanism to deter opportunistic managers; as a result, managers tend to ignore market signals in M&A deals. We find that managers of cross-listed firms from strong shareholder protection countries are more likely to listen to the market. Further analysis indicates that the likelihood to listen to the market differs by host market. While we do not find an association between cross-listing and listening to the market for firms cross-listed on the US regulated exchanges, there is some evidence that cross-listing on unregulated market affects the propensity to follow market signals. We find that listening to the market improves firm value and the impact is enhanced post cross-listing due to improvement in stock price informativeness.